2013
DOI: 10.4161/dish.27366
|View full text |Cite
|
Sign up to set email alerts
|

Trauma and PTSD rates in an irish psychiatric population

Abstract: Although Western mental health services are increasingly finding themselves concerned with assisting traumatized individuals migrating from other countries, trauma and posttraumatic stress disorder (PTSD) are under-detected and undiagnosed in psychiatric populations. This study examined and compared rates of traumatic experiences, frequency of traumatic events, trauma symptomatology levels, rates of torture, rates of PTSD and chart documentation of trauma and PTSD between (a) Irish and migrant service-users an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…Rates of PTSD and CPTSD among the current sample of treatment-seeking survivors of serious harm and torture were significantly higher than those reported in general population studies (Karatzias et al, 2019). This is not unexpected given the refugee experience is often marked by compounding instances of trauma throughout the migration journey (Crumlish & Bracken, 2011;Wilson et al, 2013). It is worth noting however, that rates of both PTSD and CPTSD were higher in the current sample than those previously observed within other treatment-seeking refugee samples still living in a refugee camp (Vallières et al, 2018), but lower than that observed in a sample of refugees resettled in the host country (Vang et al, 2019), and among resettled refugees in Switzerland (Nickerson et al, 2016).…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Rates of PTSD and CPTSD among the current sample of treatment-seeking survivors of serious harm and torture were significantly higher than those reported in general population studies (Karatzias et al, 2019). This is not unexpected given the refugee experience is often marked by compounding instances of trauma throughout the migration journey (Crumlish & Bracken, 2011;Wilson et al, 2013). It is worth noting however, that rates of both PTSD and CPTSD were higher in the current sample than those previously observed within other treatment-seeking refugee samples still living in a refugee camp (Vallières et al, 2018), but lower than that observed in a sample of refugees resettled in the host country (Vang et al, 2019), and among resettled refugees in Switzerland (Nickerson et al, 2016).…”
Section: Discussionmentioning
confidence: 47%
“…Notably, and as outlined in the United Nations Committee on the Elimination of Racial Discrimination, in their 2011 report entitled 'The Policy of Direct Provision', Ireland's inordinate delay in the processing of asylum seeker's applications and the final outcomes of their appeals and reviews, as well as poor living conditions characteristic of Direct Provision Centres, can suffer health and psychological problems that in certain cases lead to serious mental illness (UNCERD, 2011). Given that, in Ireland, up to 50% of forced migrants have suffered torture (Wilson et al, 2013), and that the physical and psychological impact of torture is often compounded by further trauma experienced during transit and on arrival in the host country, with the impact of post-transit trauma increasing over time (Beiser & Hou, 2001), the impact of the host-country experience and the psychological impact of torture often present as intertwined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of a mental health clinic in Australia, 88% of the service users assessed reported that they had experienced at least one traumatic event, with 79% reporting experiencing two or more incidence (Phipps et al, 2019). This is not a unique occurrence with other international research reflecting these findings (Kleber, 2019;Wilson et al, 2013).…”
Section: Trauma and Trauma-informed Approachesmentioning
confidence: 78%
“…A study set in inner-city Dublin reported a lifetime prevalence of PTSD of 6% in a native Irish group and 47% in a group of refugees and asylum seekers (Wilson et al , 2013 ). A 2009 cross-sectional study of 88 asylum seekers and refugees living in the west of Ireland found that asylum seekers were six times more likely than refugees to report symptoms of PTSD and depression or anxiety (Toar et al , 2009 ).…”
Section: Mental Illness Among Refugees and Asylum Seekersmentioning
confidence: 99%